2011
DOI: 10.1002/pmic.201000728
|View full text |Cite
|
Sign up to set email alerts
|

Two novel ficolin‐like proteins act as pattern recognition receptors for invading pathogens in the freshwater crayfish Pacifastacus leniusculus

Abstract: To isolate pathogen-associated molecular patterns (PAMPs)-binding molecules, the bacterium, Staphylococcus aureus was used as an affinity matrix to find bacteria-binding proteins in the plasma of the freshwater crayfish, Pacifastacus leniusculus. Two new bacteria-binding ficolin-like proteins (FLPs) were identified by 2-DE and MS analysis. The FLPs have a fibrinogen-related domain (FReD) in their C-terminal and a repeat region in their N-terminal regions with putative structural similarities to the collagen-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Far fewer studies exist on invertebrate FREPs compared to studies conducted on vertebrates [27e29]. From what we do know, the primary role of FREPs in invertebrates appears to be defense against pathogens [8,9,11,27,30,31]. This implies that invertebrate FREPs must have a large degree of flexibility so that the immune system can adequately respond to the numerous and rapidly evolving pathogens they encounter.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Far fewer studies exist on invertebrate FREPs compared to studies conducted on vertebrates [27e29]. From what we do know, the primary role of FREPs in invertebrates appears to be defense against pathogens [8,9,11,27,30,31]. This implies that invertebrate FREPs must have a large degree of flexibility so that the immune system can adequately respond to the numerous and rapidly evolving pathogens they encounter.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, we uncovered 193 FREP proteins with 205 FBG domains in C. gigas, Previous studies have reported that FREP proteins share highly conserved C-terminal FBG domains, while their N-terminal regions vary significantly, resulting in a highly diverse gene family. For example, the immunoglobulin superfamily domains in the N-terminal regions of B. glabrata FREPs [3,32] differ from FREPs in the sea squirt (Halocynthia roretzi) [6] and crayfish (Pacifastacus leniusculus) [31], which both have one short collagen-like domain. Our study further demonstrates the diversity of this gene family by uncovering multiple, overlapping FBG domains in the C. gigas FREPs we screened.…”
Section: Discussionmentioning
confidence: 99%
“…These differences might reflect the selective binding of ChFCN to E. coli K-12 but . Furthermore, these proteins could bind to A. hydrophila, E. coli as well as Staphylococcus aureus [34]. To confirm the interaction between ChFCN and E. coli K-12, an agglutination assay was performed in the presence of Ca 2þ , and the results indicated that ChFCN interacts with E. coli K-12.…”
Section: Discussionmentioning
confidence: 99%
“…forming aggregates (Gokudan et al, 1999;Kairies et al, 2001). In a crustacean, two ficolin-like proteins were recently demonstrated to bind to Gramnegative bacteria and this event was followed by the clearance of the bacteria (Wu et al, 2011).…”
Section: Fibrinogen-related Proteins In Molluscs and Arthropodsmentioning
confidence: 99%